Pengaruh Price Fairness, Influencer Marketing, dan Kualitas Produk terhadap Keputusan Pembelian ASI Booster by MamaBear di Toko Clandys Buluh Indah Denpasar - Pratiwi, Ni Putu Nilam Jati; Sri Hartati, Putu; Atim Purwaningrat, Putu (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2024)
The purpose of this study is to determine the influence of price fairness, influencer marketing, and product quality on purchasing decisions both partially and simultaneously. The research location is at Toko Clandys Buluh Indah Denpasar. The sample used was 169 respondents. The data analysis techniques used are Validity Test, Reliability, Classical Assumptions, Multiple Linear Regression, Coefficient of Determination, t Test and F Test. The results were obtained: (1) Price fairness has a significant positive effect on purchasing decisions, where t values of 7.261 and sig 0.000 were obtained. (2) Influencer marketing has a significant positive effect on purchasing decisions, where a t value of 6.127 and a sig of 0.000 is obtained. (3) Product quality has a significant positive effect on purchasing decisions, where a t value of 2.525 and a sig of 0.013 is obtained. 4) Simultaneously price fairness, influencer marketing, and product quality have a significant effect on purchasing decisions, where an F value of 48,483 and a significance of 0,000 are obtained. The magnitude of the influence of the independent variable on purchasing decisions was 46.9%. Advice that can be given to MamaBear companies to provide reasonable promotions, evaluate information provided by influencers, improve the quality of raw materials, and provide promotions regarding cash payments, especially at the Clandys Buluh Indah Store.